Atividade antimicrobiana de Derris negrensis Benth (Fabaceae) - Silva , Paulo Edson Santos da (2011)
The vegetables are excellent matter sources it excels in search of new drugs, is tended in view your diversity of molecules. The increase of infections and the emergence of microbial resistance reinforce that research. The present work had as objective evaluates the activity antimicrobial of Derris negrensis Benth (Fabaceae). The aqueous extract of stem and root of D. negrensis was obtained by the maceration method, and submitted to the evaluation of antimicrobial activity by the diffusion method in agar - technique of the well for the personal microorganisms: S. aureus, C. albicans, K. pneumoniae, P. aeruginosa and E.coli. The fungicide and bactericide activities were analyzed using plates of Petri properly prepared with middle of culture specific for each personal microorganism. The extract was preparated in the concentrations of: 300, 400 and 500mg/mL.The determination of the Minimal Inhibitory Concentration (MIC) it was done through the microdilution method in plate, front to the personal microorganisms: S. aureus, K. pneumoniae, P. aeruginosa and E.coli. Cromatography were accomplished in thin layer (PC) and bioautography. The results revealed presence of antimicrobial activity in the extract of the root for all the tested bacterias, being more effective for the bacteries S. aureus and P. aeruginosa. In the method of MIC, the extracts were capable to inhibit the microbial growth in the concentrations that varied from 75 to 300mg/mL. It was possible to observe that the extract of the root provided better antimicrobial activity in relation to the extract of the stem in the method of diffusion technical agar of the well. Substances with characteristics of: alkaloids, terpens and composed phenolics they were observed in PC. The results of this work constitute an alternative in the combat to the resistant personal micro-organisms to antibiotic and it makes possible the new derived chemical representatives' of natural products discovery, in order to minimize the microbial resistance. The continuation of complemental studies is suggested in the sense of isolating the responsible substances for this activity and the accomplishment of toxicological tests to make possible your use.